Using Video to Evaluate Depth and Velocity Selection by Arctic Grayling (Thymallus arcticus) in Pools of an Engineered Tundra Stream - Kupferschmidt, Cody; Noddin, Fred; Zhu, David Z.; Tonn, William M. (ARCTIC, 2019)
We evaluated pool use by Arctic grayling (Thymallus arcticus) in an engineered stream in the Canadian Barrenlands at the summer background flow (1.0 l/s) and at enhanced flows (9.9 l/s and 21.9 l/s) similar to those during the spring spawning period. We used an acoustic Doppler velocimeter to measure and map out point velocities (horizontal and vertical) in five study pools. The positions of adult Arctic grayling were monitored for each flow condition using visual surveys and a novel video assessment technique. Although fish mobility limited pool selection at the summer background flow, the highest use of pools by fish during enhanced flows occurred where pool designs incorporated scour holes or downstream sills to provide larger amounts of relatively deep water. Within those pools, grayling selected for locations with depths between 0.20 m and 0.30 m and near-zero vertical velocities (−0.02 m/s to 0.04 m/s). Fish selected near-zero horizontal velocities(0.00 m/s to 0.04 m/s) for resting and higher velocities (0.12 m/s to 0.20 m/s) for feeding. In contrast, grayling tended to show local avoidance of areas with horizontal velocities above 0.2 m/s or vertical velocities above 0.04 m/s. Although findings are likely site specific, our study contributes towards the development of size, depth, and velocity criteria for Arctic grayling habitat; this information can promote effective designs for habitat compensation and fish passage projects. We also present a novel video monitoring method that can be easily deployed at remote locations. Nous avons évalué l’utilisation de bassins par l’ombre arctique (Thymallus arcticus) dans un cours d’eau artificiel aménagé dans la lande canadienne au débit de base estival (1,0 l/s) et à des débits accrus (9,9 l/s et 21,9 l/s) semblables à ceux qui existent pendant la période de frai du printemps. Nous avons employé un courantomètre acoustique Doppler pour mesurer et tracer les vitesses ponctuelles (horizontales et verticales) de cinq bassins à l’étude. Les positions des ombres ...